A functional analysis of Magdalenian sites Zur Funktion von Magdalénien-Stationen - Pasda, Clemens; Weiß, Marcel (Hugo Obermaier-Society for Quaternary Research and Archaeology of the Stone Age, 2020)
The excavation of Gönnersdorf in the Rhineland in the early 1970s and the study of Weniger (1982) influence German research on the Magdalenian: lifeways of these Late Pleistocene hunter-gatherers are seen as being characterized by the presence of large base camps and associated smaller camps. This interpretation is checked by a comparison of artefacts, structures and fauna of 22 Upper Magdalenian sites from Central Germany. Main reference for interpretation are recent excavations of Upper Magdalenian sites in France and Switzerland which show what structures, artefact quantities and faunal remains were left for occupations in autumn (Pincevent-IV20), winter (Pincevent-IV0) and the warm season (Monruz, Champréveyres). The results are discussed within the context of recent research on the Magdalenian between the Atlantic and the Vistula River. The investigation reveals large commonalities in lithic tool types, in presence of stone-built hearths, in use of red color, of stone, antler and bone tools as well as in consumption of animals which were killed close to the site. This may indicate that in each Magdalenian site the same or similar activities were performed. Thus a new interpretation of Upper Magdalenian lifeways may be possible of mobile, small social units which left material records only near the kill site when, after a successful hunt, daily activities of consumption, production and retooling were perfomed in the vicinity of stone-built hearths.
CRIS-Team Scopus Importer:2024-12-16
Keywords: artefacts; Central Germany; comparative analysis; fauna; structures; Upper Magdalenian